PEDAGOGICAL INTERNSHIP AS A PRACTICALLY ORIENTED PROGRAM OF TARGETED TRAINING OF TEACHERS - S. A. Miniyurova; N. O. Leonenko; N. V. Bagicheva; M. V. Byvsheva (Вестник Мининского университета, 2017)
The article presents the experience of participation of the Ural State Pedagogical University in approbation of the model of targeted training of teachers. Analyzing the procedure for a comprehensive exam in the selection of project participants, as well as the content of targeted training, the authors justify the advisability of applying the program of pedagogical internship developed at the Ural State Pedagogical University. The content of the internship program is consistent with the goals of targeted training of teachers and values guidelines for the modernization of pedagogical education that determine the activity approach in teaching on the principles of school and university partnership, educational results as a starting point and the modular principle of designing educational programs. The structural unit of this program is a set of practical theoretical modules developed in cooperation with employers aimed at forming a certain set of professional actions that meet the requirements of the professional standard of the teacher and the sectoral specifics of the educational environment.